2013
DOI: 10.1074/jbc.m112.443952
|View full text |Cite
|
Sign up to set email alerts
|

Plant ALDH10 Family

Abstract: Background: Plant aminoaldehyde dehydrogenases (AMADHs) detoxify -aminoaldehydes from several metabolic pathways. Results: Two of five new AMADHs exhibit unusual kinetic properties. A thiohemiacetal intermediate was trapped in a crystal structure. Conclusion: Five critical residues can modulate substrate specificity, and a new substrate was identified. Significance: The present findings allow sequence-based predictions of AMADH substrate specificity linked with the production of individual osmoprotectants in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…7 B, D) . Co-BD is formed by the three main chain carbonyl groups of an isoleucine/valine (I25 in sa AldA), a glutamate/aspartate (E91 in sa AldA) and a glutamate residue (E173 in sa AldA) [60] , [61] , [62] . The cation bound at this site is usually sodium or potassium, and it was reported that the enzyme activity is slightly higher in the presence of sodium [60] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 B, D) . Co-BD is formed by the three main chain carbonyl groups of an isoleucine/valine (I25 in sa AldA), a glutamate/aspartate (E91 in sa AldA) and a glutamate residue (E173 in sa AldA) [60] , [61] , [62] . The cation bound at this site is usually sodium or potassium, and it was reported that the enzyme activity is slightly higher in the presence of sodium [60] .…”
Section: Resultsmentioning
confidence: 99%
“…In the sa AldA structure, a magnesium ion is present at this site, most likely because magnesium was the only cation present in the crystallization solution. The role of the cation-binding site is to maintain the structural integrity of the protein and to stabilize a loop involved in binding of NAD + [60] , [61] , [62] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BADHs resemble ALDH in structure and are composed of a Rossmann-fold NAD(P)-binding domain, a catalytic (substrate-binding) domain and an oligomerization (bridging) domain (Muñ oz-Clares et al, 2010). Although BADHs have been characterized in Escherichia coli (EcBADH; PDB entries 1wnb and 1wnd; Falkenberg & Strøm, 1990;Gruez et al, 2004), B. subtilis (Boch et al, 1997), Halomonas elongata DSM 3043 (Cá novas et al, 2000), Pseudoalteromonas atlantica T6c (PDB entry 3k2w; New York SGX Research Center for Structural Genomics, unpublished work), Agrobacterium tumefaciens (AtBADH; PDB entry 3r31; New York Structural Genomics Research Consortium, unpublished work), P. aeruginosa (PaBADH; PDB entries 2wme, 2wox, 2xdr and 3zqa; Gonzá lez-Segura et al, 2009; Díaz-Sá nchez et al, 2011; A. G. Díaz-Sá nchez, L. Gonzá lez-Segura, E. Rudiñ o-Piñ era, A. Lira-Rocha, A. Torres-Larios & R. A. Muñ oz-Clares, unpublished work) and in eukaryotic organisms such as Gadus morhua (GmBADH; PDB entries 1a4s and 1bpw; Johansson et al, 1998), Pisum sativum (PsBADH; PDB entries 3iwk and 3imj; Tylichová et al, 2010), Spinacia oleracae (SoBADH; PDB entry 4a0m; Díaz-Sá nchez et al, 2012) and Solanum lycopersicum (SlBADH; PDB entries 4i8p, 4i9b and 4i8q; Kopečny et al, 2013), questions remain about the molecular mechanism of action of BADH.…”
Section: Introductionmentioning
confidence: 99%
“…While the involvement of ALDH9A1 in the production of the GABA neurotransmitter from ABAL was discussed in the past [6], its role in degradation of APAL or GBAL has not been considered at all. These aldehydes were previously deeply studied for plant ALDH10 family, the closest relative of the ALDH9 family [20,21].…”
Section: Discussionmentioning
confidence: 99%